A Content Analysis of Digital Edutainment for Disaster Literacy in Higher Education - Prasetyaningsih, Prasetyaningsih; Kaniawati, Ida; Riza, Lala Septem; Utama, Judhistira Aria (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2025)
Disaster literacy is a crucial competency for communities at risk of natural hazards, especially for higher education students who will significantly contribute to future preparedness efforts. This research aimed to examine the efficacy of digital edutainment, including films and interactive content on platforms such as YouTube, TikTok, Instagram, and Coursera, in improving disaster literacy. We conducted a qualitative content analysis of materials concerning disaster knowledge, attitudes, and practical skills pertinent to mitigation and emergency response. Results indicate that edutainment effectively enhances foundational knowledge and promotes proactive attitudes; however, practical skills, including evacuation procedures and preparedness drills, are inadequately represented. It is advisable to collaborate with scientific agencies such as BMKG and BNPB to ensure the accuracy and relevance of content. This research emphasises the importance of incorporating edutainment into higher education curricula as an effective combination of learning and entertainment, supporting a comprehensive approach that integrates knowledge, attitudes, and skills to enhance societal preparedness for future disasters.